Fluctuating and Geographically Specific Selection Characterize Rapid Evolution of the Human KIR Region - Augusto, Danillo G.; Norman, Paul J.; Dandekar, Ravi; Hollenbach, Jill A. (Frontiers in Immunology, 2019)
The killer-cell immunoglobulin-like receptor (KIR) is a fast-evolving family of genes that encode receptors for natural killer (NK) cells and have crucial role in host defense. Evolution of the KIR genes was examined in the context of the human genome. Gene-content diversity and single nucleotide polymorphisms (SNP) in the KIR genes and flanking regions were compared to >660,000 genome-wide SNPs in over 800 individuals from 52 populations of the human genome diversity panel (HGDP). KIR allelic diversity was further examined using next generation sequencing in a subset of 56 individuals. We identified the SNP rs587560 located in KIR3DL3 as a marker of KIR2DL2 and KIR2DL3 and, consequently, of Cen A and Cen B haplotypes. We also show that combinations of two KIR2DL4 SNPs (rs35656676 and rs592645) mark KIR3DL1 and KIR3DS1 allelic groups and define the major KIR3DL1 high- and low-expressing alleles lineages. Comparing the diversity of the SNPs within the KIR region to all analyzed genomic markers, we observed a high diversity for the centromeric KIR region, consistent with balancing selection, in Oceanic populations (p < 0.01); in contrast, centromeric KIR diversity is significantly reduced in East Asian populations (p<0.01), indicating purifying selection. By analyzing extended SNP haplotypes in a region spanning approximately 500 kb that includes the KIR cluster, we observed evidence of strong positive selection in Africa for high-expressing KIR3DL1 alleles, favored over the low-expressing alleles (p < 0.01). In sharp contrast, the strong positive selection (p < 0.01) that we also observed in the telomeric KIR region in Oceanic populations tracked with a high frequency of KIR3DS1. In addition, we demonstrated that worldwide frequency of high-expression KIR3DL1 alleles was correlated with virus and protozoa load (r = 0.72, p < 10-5), which points to selection globally on KIR3DL1 high-expressing alleles attributable to pathogen exposure.